2022
DOI: 10.1088/1742-6596/2392/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Implementation Learning Media Based on Augmented Reality in Elementary School in Improving Critical Thinking Skills in Solar System Course

Abstract: This research aims to explore students’ critical thinking skills in Augmented reality-based learning media implementation on solar system lessons in elementary school. Critical thinking skills at the elementary school level are still relatively low due to the lack of application of learning media that support the improvement of critical thinking skills. Learning media is a very important part of learning. Research design compares modern classes (experimental classes) with control classes. Teaching using augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The first research was conducted by Andriani and Ramadani [37] who discussed the effect of using AR media on students' critical thinking skills. The next research was conducted by Zuniari et al [38] who also discussed the effect of AR media on students' critical thinking skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first research was conducted by Andriani and Ramadani [37] who discussed the effect of using AR media on students' critical thinking skills. The next research was conducted by Zuniari et al [38] who also discussed the effect of AR media on students' critical thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the research conducted by Santi et al [31] who found that AR-based textbooks can improve student learning outcomes. The use of AR in learning about the solar system in primary school can also improve students' critical thinking skills [37], [38]. The use of AR can also increase students' scientific literacy [29].…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini dapat menunjukkan bahwa augmented reality belum dikenalkan pada guru sekolah dasar secara menyeluruh. Keadaan kurangnya pengetahuan partisipan terhadap penggunaan augmented reality didukung oleh pendapat ahli yang menyatakan bahwa penggunaan augmented reality sebagai media pembelajaran di Sekolah Dasar masih kurang, sehingga membutuhkan inovasi dalam melaksanakan pembelajaran di sekolah dasar (Zuniari, Ridlo, Wahyuni, Ulfa, & Dharmawan, 2022). Sementara, augmented reality sangat diperlukan dalam pembelajaran di Sekolah Dasar karena sesuai peserta didik tingkat Sekolah Dasar masih berpikir konkret.…”
Section: Pembahasanunclassified
“…Moreover, Zuniari et al (2022) looked into how augmented reality can support knowledge acquisition and critical thinking in the context of a solar system course in primary education. Their study followed a quasi-experimental design and a total of 56 primary education students (experimental group: 28 students and control group: 28 students) participated.…”
Section: Augmented Reality In Astronomy Educationmentioning
confidence: 99%